Socio-economic profile and challenges of fishing communities:A Case study of Chhirpani Reservoir in Kabirdham district, Chhattisgarh - Beishamayum, Nightingale Devi; K, Kiran; Kaiwart, Lavanya; Bhaskar, Rakesh; Dhruw, Vidya (Journal of Indian Fisheries Association, 2023)
Fisheries plays a vital role in offering sustenance, job opportunities, and entrepreneurial avenues to over 2.8 crore individuals engaged in fishing and aquaculture at the grassroots level with thousands of people across the entire value chain (Department of Fisheries, 2023). India holds the distinction of being the global leader in inland capture fish production (SOFIA, 2022). Notably, the inland fisheries and aquaculture have surged twofold, rising from 61.36 lakh tons in 2013-14 to 121.12 lakh tons by 2021-22. The present study aims to provide an assessment of the socio-economic status and challenges of the fisher community in Chhirpani Reservoir, located in Kabirdham, Chhattisgarh. The primary data for socio-economic assessment and challenges were collected through qualitative research using semi-structured questionnaires and in-depth interviews with fishermen. The findings highlighted the dominant age group of fishers falling within 40-59 years, with male representation of 75%. Moreover, it was observed that 57% of fishers reside in Pucca houses constructed under the "Pradhan Mantri Awaas Yojna" scheme. The absence of a primary healthcare center in their villages necessitates an arduous 7-kilometer journey to access healthcare services, resulting in increased expenditure. Additionally, the study revealed that 52% of fishers have received only primary education and 35% were found to be illiterate. Subsequently, challenges they faced were discussed emphasizing the need for improved infrastructure, including health centers and schools in fishing villages, to uplift fishers’ welfare and their standard of living. By addressing these challenges, the policymakers and stakeholders can contribute to the sustainable development and well-being of the fisher community in Chhirpani reservoir.